2017
DOI: 10.1097/md.0000000000005678
|View full text |Cite
|
Sign up to set email alerts
|

Hypersomnia due to injury of the ventral ascending reticular activating system following cerebellar herniation

Abstract: Rationale:We report on a patient with hypersomnia who showed injury of the lower ascending reticular activating system (ARAS) following cerebellar herniation due to a cerebellar infarct, detected on diffusion tensor tractography (DTT).Patient concerns:A 53-year-old male patient was diagnosed as a left cerebellar infarct, and underwent decompressive suboccipital craniectomy due to brain edema at 2 days after the onset of a cerebellar infarct. Three weeks after onset when the patient started rehabilitation, he s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Many studies report an association between injury of the hypothalamus with sleep disorders, such as narcolepsy and hypersomnia, following TBI (Baumann et al, 2005 , 2009 ; Valko et al, 2015 ; Jang and Kwon, 2016 ; Jang et al, 2016b , c ; Jang and Lee, 2017 ). In addition, since the reconstruction of the ARAS using DTT is possible, many studies have demonstrated that the lower ventral ARAS, which is connected to the hypothalamus, is closely related with hypersomnia following brain injury (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ). Therefore, the results of our study appear to be consistent with previous studies (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies report an association between injury of the hypothalamus with sleep disorders, such as narcolepsy and hypersomnia, following TBI (Baumann et al, 2005 , 2009 ; Valko et al, 2015 ; Jang and Kwon, 2016 ; Jang et al, 2016b , c ; Jang and Lee, 2017 ). In addition, since the reconstruction of the ARAS using DTT is possible, many studies have demonstrated that the lower ventral ARAS, which is connected to the hypothalamus, is closely related with hypersomnia following brain injury (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ). Therefore, the results of our study appear to be consistent with previous studies (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the reconstruction of the ARAS using DTT is possible, many studies have demonstrated that the lower ventral ARAS, which is connected to the hypothalamus, is closely related with hypersomnia following brain injury (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ). Therefore, the results of our study appear to be consistent with previous studies (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, diffusion tensor tractography (DTT), which is derived from diffusion tensor imaging (DTI), provides the unique advantage of the 3-dimensional visualization and estimation of neural tracts. [ 7 9 ] In the current report, we used DTT to examine the corticofugal tracts (CFTs) from the SMAs in a patient with PD who showed LKA.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the patient’s impaired consciousness showed a good response to medication especially methylphenidate. Based on these results, we suggest the patient might have impaired consciousness and hypersomnia because the main lesion in his ARAS was located in the right lower ventral ARAS, a region related to hypersomnia following brain injury [ 4 ]. This case study suggests that an accurate diagnosis based on the state of ARAS on DTT would be helpful in achieving successful rehabilitation in patients with impaired consciousness following acute brain injury.…”
mentioning
confidence: 99%